Introduction: New Directions in Negotiation and ADR - Karen Tokarz; Rebecca Hollander-Blumoff (Washington University Journal of Law & Policy, 2012)
In Winter 2011, the Washington University Negotiation and Dispute Resolution Program joined forces with Journal to host a scholarship roundtable titled New Directions in Negotiation and ADR. The participants explored exciting, cutting edge issues in negotiation and ADR, and this remarkable volume is the product of that roundtable. The authors in this volume are at the forefront of innovative teaching, practice, and scholarship in negotiation and dispute resolution. Perhaps now more than at any other time in recent history, the practice of law is changing in unexpected ways. New professional roles for lawyers are evolving and legal education is under intense pressure to undertake curricular reforms. Litigation is no longer the default dispute resolution method. ADR—an umbrella term for a range of dispute resolution processes that occur largely outside the courts and includes negotiation, conciliation, mediation, dialogue facilitation, consensus-building, and arbitration—has emerged as a principal mode of legal practice in virtually every legal field and in virtually every country in the world.
Keywords: Alternative dispute resolution (ADR); Dispute resolution (Law); Negotiation; Legal education -- innovative approaches; Teaching methods; Law schools -- courses; Lawyering; Legal ethics; Values-based dispute (VBD); Legal clinics